Kinetic study of protein formation and digestion by quartz crystal microbalance - Tippavan Hongkacharn (2018)
Quartz crystal microbalance technique was used to study kinetic of formation and digestion of bovine serum albumin (BSA) protein on polystyrene-co-maleic acids (PSMA) surface. The kinetic of formation and digestion of BSA was investigated by measuring the frequency shift and resistance shift as a function of time. In order to study pH and concentration effect to layer formation kinetic, the pH of solution was varied from 2.0 to 7.4 while the concentration of BSA was varied in the range of 0.001 to 10 mg/ml. The kinetic of formation appears to be sensitive to the pH of solution and concentration. The formation layer at about pH 3.0 to 3.5 gives the different characteristic from the others. The layer formation increases as the concentration increase then reached the saturate value at the concentration of over 3 mg/ml. The kinetic of digestion was evaluate by applying proteinase enzyme on varies densities of BSA layer. It found that the rate of digestion depends on the density of the molecular BSA packing, modified by varying pH and concentration of BSA. ©2010 IEEE.